The financial satisfaction of personal retirement planning among Malaysian youth EPF contributors during Covid-19 pandemic - Ngo, Yu Xun; Pong, Yi Xiang; Saw, Min Zher (2022)
Throughout the research, there would be a total 7 variables to be applied which included 1 dependent variable (DV financial satisfaction of retirement planning), 3 independent variables (IV1 retirement planning, IV2 financial literacy, IV3 financial saving behaviour) and 3 mediator variables (MV1 education level, MV2 income level, MV3 age). The life cycle theory, theory of planned behaviour (TPB), and permanent income theory are well justified to fit with those variables where IV1 retirement planning, IV2 financial literacy, MV3 age are belong to the category of life cycle theory while theory of planned behaviour (TPB) represents by DV financial satisfaction of retirement planning, IV3 financial saving behaviour and MV1 education level. The permanent income theory for MV2 income level. Since mediator variables were constructed in this research, thus, when organising the 12 research objectives and hypothesis developments, the direct effect between IV to DV and indirect effect from IV to MV then DV would run simultaneously in order to verify the occurrence and the absence of mediating effect. This study is held in a primary data online Google Form questionnaire with the targeted respondent’s Malaysian youth EPF contributors who are under the age range 15 to 30 years old and staying at one of the states in Malaysia during the COVID-19 pandemic period. A total of 40 questions regarding the investigation of research variables plus 3 fill in the blank qualifications checking questions would be disclosed to eliminate unrelated respondents from the study. To add on, a total of 411 valid questionnaires which included 50 pilot test samples and 361 actual samples have been received and further studied through data analysis. By applying the SmartPLS 3, only 4 out of 12 hypothesis developments showed to be statistically significant while the rest are all statistically insignificant. With the overall result given, it means that during the COVID-19 period the targeted respondent’s Malaysian youth EPF contributors were dissatisfied towards satisfaction of retirement planning. All prospective parties such as investors, Malaysian government, Malaysian central bank, Employee Provident Fund (EPF), and future researchers are advised to apply this research outcome for any future usages.